Youth ministry in action against the fundamental concerns of today's youth (2020)
When inquiring about the actions carried out by the church from the Youth Ministry, it was found that this is a way of responding to the big questions and fundamental concerns that youth face at different times. The importance of incorporating the gospel, the value that the church gives young people and finally the pedagogy and methodology used by youth ministry to carry out the message of hope is developed. Finally, it is appreciated that, with the help of different lines of action, we try to respond to the needs of integral formation, consolidating as a pastoral of joy, showing a different face of Christ: The young face.